DETECTION OF TRANSGENERATIONAL GENETIC EFFECTS BASED ON WHOLE-GENOME SEQUENCING IN THE MOUSE MODEL. Issue 13 (9th September 2022) - Gondo, Yoichi
Abstract: It has become feasible to detect de novo mutations in mammalian genomes by using whole-genome sequencing. The power to detect numbers of de novo mutations should provide a useful tool to assess the transgenerational genetic effects of radiations on living organisms. By reviewing the spontaneous mutations in the mouse as a model, an action plan is proposed to detect the induced mutations after accumulating mutations for several generations with continuous exposure to low-dose radiations. Some susceptibility differences against radiations between humans and model animals for the transgenerational effect have been suggested. The applicability of the mouse model for the assessment of low-dose radiation is also discussed.